Visible-light-mediated synthesis of 3, 4, 5-trisubstituted furan-2-one derivatives via a bifunctional organo photocatalyst. (29th September 2021) - Dutta, Arup; Patra, Sumit Kumar; Khatua, Snehadrinarayan; Nongkhlaw, Rishanlang
Abstract : This protocol demonstrates sustainable synthesis of furan-2-one derivatives using organo photocatalyst under visible-light irradiation and DFT studies of the compound. Abstract : Furan-2-one derivatives are of great importance in chemistry for both synthetic and biological purposes. Herein, we report a new approach towards their synthesis via a mild, inexpensive, and green photochemical protocol, where dual analyte thioureas, 1 (1 H -benzo[ d ]imidazol-2-yl)-3-(4-nitrophenyl)thiourea (BINPT) and 1-(4-methylbenzo[ d ]thiazol-2-yl)-3-(4-nitrophenyl)thiourea (MBNPT), are utilized as the catalyst and white LEDs as the light source via electron donor–acceptor (EDA) complexes. A variety of diethyl 2-(phenylamino)fumarates and aldehydes were converted into 3, 4, 5-trisubstituted furan-2-ones in good to high yields. Selected compounds were further studied using DFT calculations in order to establish a clear picture about the geometric parameters of the compounds.